2008
DOI: 10.2166/wst.2008.669
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) reduction in activated sludge bacteria exposed to high chromium loading

Abstract: A mixed-culture of bacteria collected from a wastewater treatment plant in Brits, North-West Province (South Africa) biocatalytically reduced Cr(VI) at much higher concentrations than previously observed in cultures isolated in North America. Complete Cr(VI) reduction in aerobic cultures was achieved at a high concentration of 200 mg/L after incubation for only 65 hours. Under anaerobic conditions up to 150 mg, Cr(VI)/L was completely removed after incubating for 130 to 155 hours, still higher than the Cr(VI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Molokwane et al . () also demonstrated that microcosm inoculated with Cr(VI)‐reducing bacteria (R5) achieved significant removal of Cr(VI).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Molokwane et al . () also demonstrated that microcosm inoculated with Cr(VI)‐reducing bacteria (R5) achieved significant removal of Cr(VI).…”
Section: Discussionmentioning
confidence: 92%
“…Similar results were found by Srivastava and Thakur (2006) testing different Cr(VI) concentrations (200 and 400 mg kg À1 ) on soil inoculated with A. niger (FK1), which indicated that lower concentration of chromate (250 ppm) was reduced (75%) at 15 days compared with the control (5%), and chromium was removed by bioaccumulation in the mycelium of the fungus. Molokwane et al (2008) also demonstrated that microcosm inoculated with Cr(VI)-reducing bacteria (R5) achieved significant removal of Cr(VI).…”
Section: Discussionmentioning
confidence: 94%
“…The regeneration of adsorbent is quite crucial for the process to be cost-effective as well for the recovery of metal ions from the solution. In the present study, desorption was studied at different solution pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The result, as can be seen from Figure 6, indicates that the maximum desorption of 82.6% occurred at a pH of 8.…”
Section: Regeneration and Reusability Of Adsorbentsmentioning
confidence: 71%
“…The batch adsorption experiments were conducted by varying several parameters, namely pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), temperature (20 C-50 C), adsorbent dosage (5 g/L-15 g/L), and initial Cr(VI) concentration (50 ppm-150 ppm), keeping the volume of the solution at 50 mL for every run. The solutions were agitated using a magnetic stirrer at 210 rpm.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…isolated from environment [104]. A bacterial strain of the genus Microbacterium was able to reduce Cr(VI), included in a mixed culture [105], moreover, immobilized cells of a strain Microbacterium sp. showed the capability to reduce Cr(VI) [106] [56].…”
Section: Resultsmentioning
confidence: 99%